Quantitative evaluation of adhesion of osteosarcoma cells to hydrophobic polymer substrate with tunable elasticity - Yoshikawa, Hiroshi; Marx, Astrid; Engel, Ulrike; Tanaka, Motomu (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2012)
We investigated a potential application of hydrophobic poly(n-butyl acrylate) networks (cPnBA) as substrates with tunable elasticity for culturing, maintenance, and regulation of human osteosarcoma cells (U2OS). Nanoindentation experiments with an atomic force microscope revealed that the mechanical properties of cPnBA films are maintained under aqueous conditions, confirming that the substrate elasticity can be controlled simply by the degree of cross-linking, independent from the culture medium. We found that the adhesion U2OS cells to cPnBA substrates could be improved by surface treatments such as oxgen plasma and serum proteins. To determine the strength of cell adhesion, the critical pressure to detach cells from cPnBA substrates was measured using a shock wave induced by an intensive picosecond laser pulse. A monotonic increase in the cell adhesion strength in accordance with the substrate elasticity demonstrated the potential of intrinsically hydrophobic cPnBA as a new class of substrate material with tunable mechanical properties that are not influenced by the culture medium.